THE ROLE OF SAVINGS AND LOAN COOPERATIVES IN HELPING ACCESS TO CAPITAL FOR MSMES IN TUBAN REGENCY - Alviana Dwi Liswahyuni; Isa Anshori (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2026)
PURPOSE - MSMEs in Tuban Regency play an important role in the regional economy, but are still constrained by access to capital. Savings and Loan Cooperatives (KSP) are an alternative solution because of easy requirements, low interest rates, and business assistance.METHODOLOGY - This research was conducted at the Cooperatives, SMEs, and Trade Office of Tuban Regency using qualitative methods. The main source of data comes from primary data, obtained through direct observation and interviews with the Head of the Cooperatives Division, and one of the employees in the cooperative sector at the Institution. Savings and Loan Cooperatives in Tuban play an important role in assisting access to capital for MSMEs through inclusive financing and business training. Cooperatives also build social values such as mutual cooperation and responsibility.FINDING - Despite facing challenges such as low financial literacy and governance, cooperatives still have the potential to be sustainable drivers of the local economy. Therefore, institutional strengthening, increasing member participation, and external support from the government and strategic partners are key to making cooperatives the main pillar of MSME empowerment and sustainable people's economic development in Tuban.